Obat Rajo Obat Ditawar : Tumbuhan Obat dan Pengobatan Tradisional Masyarakat Serampas – Jambi 1 - Hariyadi, Bambang (Universitas Jambi, 2011)
Serampas is an indigenous group of Jambi who still live traditionally. Serampas has a number of traditional knowledge related to local natural resources, including medicinal plants. This study aims to reveal the Serampas view about illness and the types of herbs they use. Research conducted by methods of participant observation, survey respondents, as well as in-depth interviews. The results showed that the community Serampas classifies herbs into two main groups: obat rajo and obat ditawar. The Serampas use more than 131 species of medicinal plants. Although forests around the Serampas settlements are relatively undisturbed and rich in various plants, including medicinal plants, however, unexpectedly, most medicinal plant not derived from natural forests, but from the human made ​​ecosystem, mainly scrubland and agricultural areas.